Pengaruh Content Marketing Terhadap Minat Beli Dan Emotional Marketing Sebagai Variabel Intervening - Renwarin , Joseph M. J.; Kamalsyah, Ferry (Research and Community Service UNIVERSITAS KALBIS, 2024)
Pocari Sweat advertises using anime media and gets 15 million views on YouTube, from the pre-survey it is known that respondents are interested in anime advertising rather than the advertising product. This study aims to find out how much Content Marketing has an effect on Purchase Intention, how much Content Marketing has an effect on Emotional Marketing, how much Emotional Marketing has an effect on Purchase Intention and how much Emotional Marketing intervenes in the influence of Content Marketing on Purchase Intention. This research method uses a quantitative approach method and the Probability Sampling method in sampling respondents. The results of this study are content marketing has a positive and significant relationship to Purchase Intention, content marketing has a positive and significant relationship to emotional marketing, emotional marketing has a positive and significant relationship to Purchase Intention, Emotional Marketing intervenes in the influence of Content Marketing on Buying Interest by The value of the indirect influence of Content Marketing through Emotional Marketing on Purchase Interest is 0.363 > from the direct influence with a value of 0.273